Penilaian Evaluasi Kinerja Menggunakan Metode Behaviorally Anchored Rating Scale (BARS) di PT. Gaji Pintar Indonesia - Eni Sukmawati; Abel Adhaprilliani; Yurisma Pertiwi; Samsul Hidayat (Master Manajemen, 2025)
The purpose of this study is to compare how PT Indonesia Nippon Saiki and PT Gaji Pintar Indonesia assess performance using a rating scale based on behavior (BARS). The BARS method was chosen because it can describe specific behaviors to provide a more objective and measurable assessment. The research was conducted through questionnaires and interviews with employees and managers from both companies. The analysis results indicate that the implementation of BARS at PT Indonesia Nippon Saiki is more structured and consistent. In contrast, the implementation of BARS at PT Gaji Pintar Indonesia tends to be more flexible but less systematic. These findings provide insights into the effectiveness of the BARS method in improving the quality of performance evaluations and offer recommendations for the best method to be applied in companies. It is hoped that this research will help other companies use better performance evaluation methods.